Massage therapy for home care patients using the health insurance system in Japan. (February 2018) - Kondo, H.; Ogawa, S.; Nishimura, H.; Ono, A.
Highlights: To clarify the status of home care massage services provided to patients. This will be reference data for the future examination of home care services. Abstract: Objectives: To clarify the status of home care massage services provided to patients. This will help in understanding how many patients utilize this service and the circumstances under which treatment is provided. Design: A retrospective study. Setting: Fifty-four acupuncture, moxibustion, and massage clinics. Participants were patients who had received home care massage for six months or more. We collected a total of 1587 responses from these 54 massage clinics; of these, 1415 responses (mean age = 79.1 ± 11.5 years) were valid (valid response rate 89.2%). Main outcome measures: Actual patients and actual care services. Results: The most common disorder observed among patients who utilized home care massage services was cerebrovascular disease (at approximately 36%), while the second most common were arthropathy-related disorders (16.3%). Although most patients received massage, approximately 30% received manual therapy (e.g. manual correction) and hot fomentation as part of thermotherapy. Notably, only around 10% of patients received massage alone; the majority received treatment in combination with range of motion and muscle-strengthening exercises. Conclusions: This study helped to clarify the actual state of patients receiving home care massage and the details of the massage services provided. This study clearly showed the treatment effectiveness of massage, which can be used by home medical care stakeholders to develop more effective interventions.